Analysis of Myth Barthes in SGM Milk Formula Advertisement “Aku Anak SGM Explore” Version - Rima Novia Ulfa; Rr. Astri Indriana Octavita; Tiarma Ika Yuliana (Scope : Journal of English Language Teaching, 2021)
Advertisement is a medium of communication between producers and consumers. An advertisement can be done through various media such as newspapers, magazines, internet, radio and/or television. In advertisement, producers try to create a sign to make a hidden message (mitos) behind.  Advertisement plays significant role in promoting such products because it spreads wider. Literacy of advertisements, through mass media is very essential in helping audiences to better see and understand how messages in the form of text, verbal and nonverbal are displayed through audio visual. The hidden message is created to convey consumers. So that, they can truly understand the message. Television is as one of the media to represent hidden message contained in an advertisement.This study aims to analyze how the signs contained in the texts displayed in the SGM formula advertisement, version "Aku Anak SGM" on television. The methodology used was qualitative with a semiotic analysis approach. Semiotic approach from Barthes will be used by researchers to reveal the signs in these advertisements, by using signifier and signified to get hidden meaning inside. From this analysis can be revealed signs that are relevant to the message that the producer wants to assure the consumers. The existence of advertisements in audio-visual media with other media certainly has a different effect. Television is a complete media, because it can contain messages in the form of audio and visually. Commercial advertisements will have more selling power if they succeed in taking advantage of the advantages possessed by the media.